Detecção de ciclistas em cenário urbano por meio de visão computacional em dispositivos móveis - Santos, Leandro Alves dos (2024)
Automatically detecting and counting cyclists in urban scenarios is a task in intelligent transportation systems and smart cities that enables the generation of important structured data. This data contributes to understanding the dynamics of cyclists’ use of the urban space and guides the development of public policies for cycling mobility and traffic safety. In this study, we propose an embedded system for cyclist detection and counting, aiming to be a lightweight solution using computer vision and deep learning methods. It is characterized by low energy consumption and easy handling, based on the Raspberry Pi 4 platform and the Edge TPU Coral accelerator. The developed system achieved an F1-score of 0.9137 for processing pre-recorded video. In field counting experiments, where the system’s count was compared to human count, it resulted in counting performance between 78.3% and 82.2% in relation to visual counting.